The Influence of Quiz-Based Problem-Based Learning (PBL-Q) on Biology Concept Mastery among Students with Different Academic Abilities - Any Fatmawati; Saidil Mursali; I Wayan Karmana (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study was to determine the effect of Problem Based Learning based on Quiz (PBL-Q) on students' mastery of biology concepts in terms of academic ability. The number of research participants was 62 Biology Education students at Universitas Pendidikan Mandalika. The study was conducted in the odd semester of the 2023/2024 and 2024/2025 academic years. The research material was from the plant physiology course. The instrument used to assess concept mastery was an essay test on Plant Physiology consisting of 11 valid and reliable questions. Data were analyzed using the Ancova test with a significance level of 5%. The results of the study showed that: a) there were differences in students' mastery of biology concepts based on learning models, students who used the PBL-Q model had better mastery of biology concepts than students who used the PBL model; b) there were differences in students' mastery of biology concepts based on academic ability, students with high academic ability were better than students with low academic ability; c) there were differences in students' mastery of biology concepts based on the interaction between the learning model and students' academic ability. Based on LSD notation, students' mastery of biology concepts is ranked from highest to lowest: PBL-Q students with high academic ability, PBL-Q students with low academic ability, PBL students with high academic ability, and PBL students with low academic ability. The findings of this study indicate that the PBL-Q learning model can help students improve their mastery of biology concepts in terms of academic ability, especially in Plant Physiology material